The association between continuous antibiotic prophylaxis and UTI from birth until initial postnatal imaging evaluation among newborns with antenatal hydronephrosis. Issue 6 (December 2018) - Varda, B.K.; Finkelstein, J.B.; Wang, H.-H.; Logvinenko, T.; Nelson, C.P.
Summary: Introduction: There is a lack of consensus regarding the use of continuous antibiotic prophylaxis (CAP) during the interval between birth and initial postnatal imaging in infants with a history of antenatal urinary tract dilation (AUTD). Objective: To determine the incidence of urinary tract infection (UTI), and the association between CAP use and UTI during the interval between birth and the first postnatal renal ultrasound (RUS) in infants with AUTD. Study design: A single-institution, retrospective cohort study of newborns with a history of AUTD. Infants undergoing RUS within 3 months of birth for an indication of 'hydronephrosis' between 2012 and 2014 were identified. A random sample of 500 infants was selected; six were excluded for concomitant congenital anomalies. Baseline patient (sex, race, insurance) and clinical characteristics (circumcision status, UTD risk score, receipt of CAP, UTI prior to RUS, age at UTI, and age at RUS) were collected via retrospective chart review. Descriptive statistics were calculated. To adjust for receipt of CAP, propensity score adjusted univariate logistic regression for UTI based on CAP status was performed. Results: Among the 494 infants with AUTD, 157 (32%) received CAP. Infants with normal/low-risk UTD scores were less likely to receive CAP than those with medium/high-risk UTD (23% vs 77%; P  < 0.001). There was no difference in CAP based on sex, insurance, or circumcision status (among 260/365 males with known circumcision status). Overall, seven infants (1.4%) developed UTI prior to imaging: six (1.8%) without CAP vs one (0.64%) with CAP ( P  = 0.44). The median age at UTI was 59 days (range 2–84); among those with UTI, initial imaging occurred significantly later (66 vs 28 days; P  = 0.001). The propensity score adjusted odds of developing UTI with CAP (vs without) was 0.93 (95% CI 0.10–8.32; P  = 0.95). The Summary Figure describes the infants with UTI. Conclusion: The incidence of UTI prior to initial neonatal imaging in newborns with AUTD was low. Use of CAP was not associated with UTI incidence after adjusting for UTD severity. Routine use of CAP in newborns with AUTD prior to initial imaging may be of limited benefit in most patients. Figure